Solid Phase Microextraction and Related Techniques for Drugs in Biological Samples - Mohammad Mahdi Moein; Rana Said; Fatma Bassyouni; Mohamed Abdel-Rehim (Journal of Analytical Methods in Chemistry)
In drug discovery and development, the quantification of drugs in biological samples is an important task for the determination of the physiological performance of the investigated drugs. After sampling, the next step in the analytical process is sample preparation. Because of the low concentration levels of drug in plasma and the variety of the metabolites, the selected extraction technique should be virtually exhaustive. Recent developments of sample handling techniques are directed, from one side, toward automatization and online coupling of sample preparation units. The primary objective of this review is to present the recent developments in microextraction sample preparation methods for analysis of drugs in biological fluids. Microextraction techniques allow for less consumption of solvent, reagents, and packing materials, and small sample volumes can be used. In this review the use of solid phase microextraction (SPME), microextraction in packed sorbent (MEPS), and stir-bar sorbtive extraction (SBSE) in drug analysis will be discussed. In addition, the use of new sorbents such as monoliths and molecularly imprinted polymers will be presented.